Analysis of the Effect of BPJS Ketenagakerjaan Death Benefits on the Socio-Economic Conditions of Heirs of Participants in the Informal Sector - Ferwina Sari Darwis; Noer Azam Achsani; Nur Hasanah (Asian Journal of Social and Humanities, 2026)
Informal workers constitute a major segment of Indonesia’s labor force and remain highly vulnerable to income shocks due to limited social protection coverage. The Death Benefit Program (Jaminan Kematian/JKM), administered by BPJS Ketenagakerjaan, serves as a key social protection mechanism for informal workers and their survivors. Using a mixed-methods approach, this study examines the effects of JKM benefits on survivors’ socioeconomic conditions and compares benefit utilization between rural and urban areas. Quantitative analysis based on the Basic Needs Approach and SEM-PLS reveals that JKM benefits have a positive and significant effect on all basic needs dimensions in both settings. The impact on food security is more pronounced in rural areas, whereas the effect on clothing needs is stronger in urban areas, reflecting differences in socioeconomic structures. Qualitative findings grounded in the Theory of Planned Behavior indicate that educational scholarships enhance educational continuity by strengthening attitudes, social norms, and perceived behavioral control. These results underscore the importance of region-sensitive social protection design for informal workers. SWOT analysis was used in this study to develop recommendations for BPJS Ketenagakerjaan in providing policies and education to improve the effectiveness of Death Benefit utilization by heirs in urban and rural areas, which resulted in a growth-oriented strategy in the form of efforts to increase social security literacy among young people, strengthen access to information and infrastructure in rural areas, and design contextual, region-based social protection policies to improve the effectiveness of JKM benefits utilization.